The nest - Oppel, Kenneth, 1967- (Simon & Schuster Books for Young Readers, 2015)
"When wasps come to Steve in a dream offering to fix his sick baby brother, he thinks all he has to do is say yes. But yes may not mean what Steve thinks it means"--